A Casting Method For Artificial Rock Specimens - Da Zhao Gu (International Conference on Ground Control in Mining, 1992)
An important problem in rock engineering is to control the properties of artificial rock. A compaction technique for casting artificial rock specimens with controlled properties is described, i.e. using a compression-testing machine to compress the mixture. Uniform density is necessary to achieve uniformity of properties of the specimens, and uniform density can be obtained by using the specific pressing method presented. Rebound and borax content are important to the technique and have been studied as well.